(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2017)
An experiment was conducted to isolate a number of biocontrol agent- Trichoderma spp. from infected spawn packets of oyster mushroom at National Mushroom Development and Extension Centre, Savar, Dhaka, Bangladesh. These bio-control agents were used as antagonist against four wild wood decay fungi of Ganoderma, viz., G. lucidum-1, G. lucidum-2, G. lucidum-3, G. applanatum and two cultivated G. lucidum-4, G.lucidum-6 under in vitro condition. An in vitro trial of Trichoderma spp. against Ganoderma were performed by dual culture, by treating with volatile, non-volatile and naturally untreated metabolites of bio-control agents. In dual culture, all the Trichoderma species showed 70- 100% mycelia inhibition of G. lucidum-1 and G. lucidum-2, 55.6-100% inhibition of G. lucidum-3, 20-66.7% of G. applanatum, 100% of G. lucidum-5, 75-100% of G. lucidum-6. Effects of heat killed extracts of Trichoderma spp. on growth of G. lucidum-2 (wild) and G. lucidum-6 (cultivated) were also evaluated. Fungicides Bavistin and Dithane M-45 were also used to investigate the mycelial growth inhibition of Ganoderma spp. Int. J. Agril. Res. Innov. & Tech. 6 (2): 31-35, December, 2016